2016
DOI: 10.1016/j.jval.2016.03.100
|View full text |Cite
|
Sign up to set email alerts
|

Costs Associated with Choice of Perioperative Intravenous Crystalloid among Adults Undergoing Cardiac Surgery

Abstract: A45Objectives: Patients undergoing cardiac surgery (CS) routinely receive intravenous (IV) crystalloids perioperatively (during and immediately post-surgery). A study using a large US electronic health record database, reported an association between the use of low-chloride IV crystalloids and improved outcomes. Here we examine the association between perioperative crystalloid choice and treatment costs among adults undergoing CS. MethOds: Patients who underwent CS between January 2009-June 2013 and received ≥… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…This limits the clinical value of the results significantly, as non-patient-important outcomes (surrogate outcomes) are known to result in inflated estimates and increased risk of false-positive findings. 50,51 Only seven studies reported patient-centred outcome measures, 20,21,23,26,34,45,46 none of which were high-quality RCTs. Importantly, no studies reported data on adverse effects.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This limits the clinical value of the results significantly, as non-patient-important outcomes (surrogate outcomes) are known to result in inflated estimates and increased risk of false-positive findings. 50,51 Only seven studies reported patient-centred outcome measures, 20,21,23,26,34,45,46 none of which were high-quality RCTs. Importantly, no studies reported data on adverse effects.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding acetate, animal studies have shown a significant increase in plasma concentrations of up to 40 times the physiological level with even small volumes of acetate-based Six studies 20,21,23,26,34,46 Five studies found no statistically significant difference between groups 20,21,23,26,34 One study found OR for 90-day mortality of 0.96 (95% CI: 0.94e0.97) in the acetate-vs lactate-buffered groups 46 Hospital LOS Five studies 21,23,26,34,45 Two studies found increased hospital LOS in the lactate-vs acetate-buffered groups 26,34 One study found increased hospital LOS in the acetate-buffered group 45 Two studies found no difference between groups 21,23 ICU LOS Four studies 20,21,23,34 No studies reported a significant difference in ICU LOS between groups 20,21,23,34…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations